Method for preparing fly ash derived high-thermal-conductivity mullite ceramic by utilizing molten salt filling

High thermal conductivity mullite ceramics were successfully prepared by mixing fly ash with an aluminum source by ball milling, sintering, and vacuum impregnation in high-temperature molten inorganic salts. This solved the problem of the inability to prepare high thermal conductivity mullite ceramics with existing technology and achieved Efficient utilization of fly ash resources.

CN119330736AActive Publication Date: 2025-01-21ZHALAI NUOER COAL IND CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411484117.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-21
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The prior art cannot use fly ash to prepare highly thermally conductive mullite ceramics, which limits its application potential in the field of heat transfer.

Method used

Fly ash and aluminum source are ball milled and mixed evenly, followed by sintering reaction and vacuum impregnation in high-temperature molten inorganic salts to prepare fly ash-derived high thermal conductivity mullite ceramics.

Benefits of technology

The preparation of fly ash-derived porous mullite ceramics has been achieved, which has high thermal conductivity and high working temperature, is suitable for large-scale industrial production, reduces costs, and improves the comprehensive utilization ability of fly ash.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330736A_ABST
    Figure CN119330736A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing fly ash derived high-thermal-conductivity mullite ceramic by utilizing molten salt filling, and relates to a method for preparing high-thermal-conductivity mullite ceramic. The invention aims to solve the problem that the high-thermal-conductivity mullite ceramic cannot be prepared from fly ash in the prior art. The preparation method comprises the following steps: 1, ball-milling and uniformly mixing crushed fly ash and an aluminum source; 2, sintering reaction; and 3, carrying out vacuum impregnation treatment in high-temperature molten inorganic salt. The method is used for preparing the fly ash derived high-thermal-conductivity mullite ceramic by utilizing molten salt filling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing high thermal conductivity mullite ceramics. Background Art

[0002] Fly ash is one of the main solid wastes generated by coal-fired power plants. It is in the form of gray or off-white fine powder, mainly composed of silicates and aluminates. Due to its tiny particles and large surface area, fly ash is easy to diffuse in the air, causing environmental pollution. Compared with the traditional landfill treatment method, the use of fly ash to prepare mullite porous ceramics not only has higher economic added value, but also reduces the environmental burden. However, due to the poor thermal conductivity of mullite itself, the existing technology cannot use fly ash to prepare mullite ceramics with high thermal conductivity, which limits its application potential in the field of heat transfer. Summary of the invention

[0003] The present invention aims to solve the problem that the prior art cannot use fly ash to manufacture high thermal conductivity mullite ceramics, and provides a method for preparing fly ash-derived high thermal conductivity mullite ceramics by filling with molten salt.

[0004] A method for preparing fly ash-derived high thermal conductivity mullite ceramics by using molten salt filling is completed by the following steps:

[0005] 1. Crush the fly ash, then mix the crushed fly ash and aluminum source by ball milling, and finally sieve to obtain a uniformly mixed powder;

[0006] 2. Sintering the uniformly mixed powder for 0.5h to 3h in an air atmosphere at a temperature of 1150°C to 1350°C, and cooling the powder in the furnace after the reaction to obtain fly ash-derived mullite ceramics;

[0007] 3. The fly ash-derived mullite ceramics are vacuum impregnated in a high-temperature molten inorganic salt, and then naturally cooled after being taken out to obtain fly ash-derived high thermal conductivity mullite ceramics.

[0008] The beneficial effects of the present invention are:

[0009] 1. In the present invention, when the mass percentage of the aluminum source in the mixed uniform powder is 14%, the prepared fly ash-derived porous mullite ceramic produces mullite whiskers with a diameter of about 100 nm and an aspect ratio of 1:7, and has an apparent porosity of 51%. Then, by introducing molten inorganic salt to fill the mullite ceramic, the thermal conductivity below the melting point of the inorganic salt is improved.

[0010] 2. The maximum operating temperature of the fly ash-derived high thermal conductivity mullite ceramic prepared in the present invention is 758°C to 893°C.

[0011] 3. The preparation method of the present invention is simple, the process is easy to control, and it is suitable for large-scale industrial production. The present invention uses fly ash as raw material, reduces costs, maximizes the high value-added resource utilization of fly ash in heat transfer related fields, and improves my country's comprehensive utilization capacity of fly ash. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a microscopic morphology of the fly ash-derived mullite ceramic prepared in step 2 of Example 3;

[0013] Figure 2 This is a comparison chart of the porosity of fly ash-derived mullite ceramics prepared in step 2 of Examples 1 to 5;

[0014] Figure 3 This is the element distribution diagram of the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 of Example 3;

[0015] Figure 4 This is a comparison chart of the thermal conductivities of the fly ash-derived mullite ceramic prepared in step 2 of Examples 1 to 5 and the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3. DETAILED DESCRIPTION

[0016] Specific implementation method 1: This implementation method is a method for preparing fly ash-derived high thermal conductivity mullite ceramics by using molten salt filling, which is completed by the following steps:

[0017] 1. Crush the fly ash, then mix the crushed fly ash and aluminum source by ball milling, and finally sieve to obtain a uniformly mixed powder;

[0018] 2. Sintering the uniformly mixed powder for 0.5h to 3h in an air atmosphere at a temperature of 1150°C to 1350°C, and cooling the powder in the furnace after the reaction to obtain fly ash-derived mullite ceramics;

[0019] 3. The fly ash-derived mullite ceramics are vacuum impregnated in a high-temperature molten inorganic salt, and then naturally cooled after being taken out to obtain fly ash-derived high thermal conductivity mullite ceramics.

[0020] Principle: Fly ash contains substances such as silicon dioxide. Using fly ash as raw material, aluminum source is introduced as reactant, and 3Al is achieved after reaction under high temperature environment. 2 O 3 ·2SiO 2 Mullite component.

[0021] The formation of high-hardness mullite ceramics prepared by reaction mainly follows the following chemical reaction process:

[0022] Formation of Mullite:

[0023] SiO2 (Quartz phase) → SiO 2 (Cristallite Phase)

[0024] SiO 2 (Quartz phase)+SiO 2 (cristobalite phase) → SiO 2 (Liquid amorphous phase)

[0025] 3Al 2 O 3 +2SiO 2 (liquid amorphous phase) → 3A1 2 O 3 ·2SiO 2 (Mullite phase).

[0026] The beneficial effects of this embodiment are:

[0027] 1. In this embodiment, when the mass percentage of the aluminum source in the mixed uniform powder is 14%, the prepared fly ash-derived porous mullite ceramic produces mullite whiskers with a diameter of about 100 nm and an aspect ratio of 1:7, and has an apparent porosity of 51%. Then, by introducing molten inorganic salt to fill the mullite ceramic, the thermal conductivity below the melting point of the inorganic salt is improved.

[0028] 2. The maximum operating temperature of the fly ash-derived high thermal conductivity mullite ceramic prepared in this embodiment is 758°C to 893°C.

[0029] 3. The preparation method of this embodiment is simple, the process is easy to control, and it is suitable for large-scale industrial production. This embodiment uses fly ash as raw material to reduce costs, maximize the high value-added resource utilization of fly ash in heat transfer related fields, and improve my country's comprehensive utilization capacity of fly ash.

[0030] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the fly ash is crushed into blocks with a size of less than 75 μm in step 1. The rest is the same as the specific implementation method 1.

[0031] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the aluminum source in step 1 is one or a combination of aluminum oxide, bauxite and kaolin. The rest is the same as specific implementation method 1 or 2.

[0032] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the ball milling in step 1 is carried out for 2h to 6h at a rotation speed of 250r / min to 400r / min and a ball-to-material ratio of (1 to 2):1. The rest is the same as specific embodiments 1 to 3.

[0033] Specific implementation mode 5: This implementation mode is different from the specific implementation modes 1 to 4 in that the sieving in step 1 is through a 200-mesh sieve. The rest is the same as the specific implementation modes 1 to 4.

[0034] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the mass percentage of the aluminum source in the uniformly mixed powder in step 1 is 0% to 28%. The rest is the same as specific implementation examples 1 to 5.

[0035] When the mass percentage of aluminum source in the mixed powder described in step 1 is 0%, since the fly ash originally contains a small amount of aluminum oxide, 3Al 2 O 3 +2SiO 2 (liquid phase amorphous phase) → 3A1 2 O 3 ·2SiO 2 (Mullite phase) reaction produces a small amount of mullite, so it still belongs to mullite ceramics.

[0036] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: in step 2, the mixed powder is first heated to 300°C to 500°C at a rate of 5°C / min to 10°C / min under air atmosphere, and then heated to 1150°C to 1350°C at a rate of 2°C / min to 2.5°C / min. The rest is the same as specific embodiments 1 to 6.

[0037] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that the high temperature molten inorganic salt in step 3 is high temperature molten sodium fluoride or high temperature molten potassium fluoride. The rest is the same as specific embodiments 1 to 7.

[0038] The melting point of the sodium fluoride is 993°C, and the melting point of the potassium fluoride is 858°C.

[0039] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the vacuum impregnation treatment described in step 3 is performed under a vacuum degree of 0.1 Pa to 1 Pa for 0.5 h to 2 h. The rest is the same as specific embodiments 1 to 8.

[0040] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that the mass percentage of inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 is 10.01% to 50.02%. Other aspects are the same as Specific embodiments 1 to 9.

[0041] The following examples are used to verify the beneficial effects of the present invention:

[0042] Embodiment 1:

[0043] A method for preparing fly ash-derived high thermal conductivity mullite ceramics by using molten salt filling is completed by the following steps:

[0044] 1. The fly ash is crushed, and then the crushed fly ash is mixed with the aluminum source by ball milling at a rotation speed of 300r / min and a ball-to-material ratio of 1:1 for 4 hours, and finally sieved to obtain a uniformly mixed powder;

[0045] 2. The uniformly mixed powder is placed in a corundum crucible, and in an air atmosphere, the temperature is first raised to 500°C at a rate of 5°C / min, and then raised to 1300°C at a rate of 2.5°C / min, and finally sintered for 2 hours in an air atmosphere at a temperature of 1300°C. After the reaction is completed, the powder is cooled in the furnace to obtain fly ash-derived mullite ceramics;

[0046] 3. Under the condition of vacuum degree of 0.1Pa, the fly ash-derived mullite ceramics were vacuum impregnated in high-temperature molten inorganic salt for 2 hours, and then naturally cooled after being taken out to obtain fly ash-derived high thermal conductivity mullite ceramics.

[0047] In step 1, the fly ash is crushed into blocks with a size less than 75 μm.

[0048] The aluminum source described in step 1 is alumina powder with a purity of 99.98%, which is sourced from Inner Mongolia Haite Huacai Technology Co., Ltd.;

[0049] The sieving described in step 1 is through a 200-mesh sieve.

[0050] The fly ash described in step 1 comes from the bulk fly ash of Inner Mongolia Zhalainuoer Coal Industry Co., Ltd., and its composition is SiO 2 Content 27.76wt%, Al 2 O 3 Content 12.78wt%, Fe 2 O 3 content 26.68wt%, CaO content 15.09wt%, MgO content 1.29wt%, Na 2 O content: 11.42wt%, K 2 O content: 4.98wt%.

[0051] The mass percentage of the aluminum source in the uniformly mixed powder described in step 1 is 0%.

[0052] The high temperature molten inorganic salt described in step 3 is high temperature molten sodium fluoride (melting point 993° C.).

[0053] The mass percentage of inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step three is 10.01%.

[0054] The maximum operating temperature of the fly ash-derived high thermal conductivity mullite ceramic prepared in step three is 893°C.

[0055] Embodiment 2: This embodiment differs from Embodiment 1 in that the mass percentage of the aluminum source in the uniformly mixed powder in step 1 is 7%; the mass percentage of the inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 is 20.32%. Others are the same as in Embodiment 1.

[0056] Embodiment 3: This embodiment differs from Embodiment 1 in that the mass percentage of the aluminum source in the uniformly mixed powder in step 1 is 14%; the mass percentage of the inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 is 30.15%. Others are the same as in Embodiment 1.

[0057] Embodiment 4: This embodiment differs from Embodiment 1 in that the mass percentage of the aluminum source in the uniformly mixed powder in step 1 is 21%; the mass percentage of the inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 is 40.83%. Others are the same as in Embodiment 1.

[0058] Embodiment 5: This embodiment differs from Embodiment 1 in that the mass percentage of the aluminum source in the uniformly mixed powder in step 1 is 28%; the mass percentage of the inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 is 50.02%. Others are the same as in Embodiment 1.

[0059] Figure 1 This is a microscopic morphology of the fly ash-derived mullite ceramic prepared in step 2 of Example 3; as can be seen from the figure, when the mass percentage of the aluminum source in the mixed uniform powder is 14%, mullite whiskers with a diameter of about 100 nm and an aspect ratio of 1:7 are produced in the final product, indicating that mullite ceramics are successfully prepared using the method of this example.

[0060] Figure 2 This is a porosity comparison chart of fly ash-derived mullite ceramics prepared in step 2 of Examples 1 to 5; as can be seen from the figure, when the mass percentage of the aluminum source in the mixed uniform powder is 14%, the prepared mullite ceramic is a porous ceramic with an apparent porosity of 51%.

[0061] Figure 3 This is the element distribution diagram of the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 of Example 3. As can be seen from the figure, when the mass percentage of the aluminum source in the mixed uniform powder is 14%, after the prepared mullite ceramic is filled with inorganic salt, the NaF inorganic salt fills the pores of the mullite porous ceramic and is evenly distributed in the ceramic.

[0062] Figure 4The thermal conductivity comparison diagram of the fly ash-derived mullite ceramic prepared in step 2 of Examples 1 to 5 and the fly ash-derived high thermal conductivity mullite ceramic prepared in step 3 is shown in the figure. As can be seen from the figure, when the mass percentage of the aluminum source in the mixed uniform powder is 14%, the thermal conductivity of the prepared mullite porous ceramic is increased from 0.6005W / (m·K) to 1.1322W / (m·K) after the inorganic salt is filled; when the mass percentage of the aluminum source in the mixed uniform powder is 28%, the thermal conductivity of the prepared mullite porous ceramic is increased from 0.4327W / (m·K) to 1.4816W / (m·K) after the inorganic salt is filled.

Claims

1. A method for preparing fly ash-derived high thermal conductivity mullite ceramics by using molten salt filling, characterized in that It is done in the following steps:

1. Crush the fly ash, then mix the crushed fly ash and aluminum source by ball milling, and finally sieve to obtain a uniformly mixed powder; 2. Sintering the uniformly mixed powder for 0.5h to 3h in an air atmosphere at a temperature of 1150°C to 1350°C, and cooling the powder in the furnace after the reaction to obtain fly ash-derived mullite ceramics; 3. The fly ash-derived mullite ceramics are vacuum impregnated in a high-temperature molten inorganic salt, and then naturally cooled after being taken out to obtain fly ash-derived high thermal conductivity mullite ceramics.

2. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that In step 1, the fly ash is crushed into blocks with a size less than 75 μm.

3. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that The aluminum source described in step 1 is one or a combination of alumina, bauxite and kaolin.

4. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that The ball milling described in step 1 is specifically performed at a rotation speed of 250 r / min to 400 r / min and a ball-to-material ratio of (1 to 2):1, and the ball milling is performed for 2 h to 6 h.

5. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that The sieving described in step 1 is through a 200-mesh sieve.

6. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by using molten salt filling according to claim 1, characterized in that The mass percentage of the aluminum source in the uniformly mixed powder described in step 1 is 0% to 28%.

7. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that In step 2, under air atmosphere, the temperature of the uniformly mixed powder is first raised to 300°C to 500°C at a rate of 5°C / min to 10°C / min, and then raised to 1150°C to 1350°C at a rate of 2°C / min to 2.5°C / min.

8. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that The high temperature molten inorganic salt in step 3 is high temperature molten sodium fluoride or high temperature molten potassium fluoride.

9. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that The vacuum impregnation treatment described in step 3 is specifically performed under the condition of a vacuum degree of 0.1Pa to 1Pa for 0.5h to 2h.

10. The method for preparing fly ash-derived high thermal conductivity mullite ceramics by molten salt filling according to claim 1, characterized in that The mass percentage of inorganic salt in the fly ash-derived high thermal conductivity mullite ceramic prepared in step three is 10.01% to 50.02%.

Citation Information

Patent Citations

  • Method for preparing mullite aggregate with waste

    CN101602599A

  • Process for preparing mullite whisker or flaky alumina by using coal ash

    CN101775659A

  • Assembly method for porous ceramic enhanced conductive inorganic salt phase change heat storage element and heat storage element formed by assembly method

    CN112284170A

  • Ceramic-based fused salt composite phase change heat storage material and preparation method thereof

    CN115432997A

  • Molding composition, molded body, and method for producing molded body

    JP2023069436A